A Case of Diaphragmatic Liver Herniation Simulating a Pulmonary Benign Tumor - Muto, Yoshihiro; Yoshimura, Yasushi; Shibata, Koichiro; Okuno, Kazuhiro; Nakatsuka, Shigekazu; Amenomori, Hiromasa; Kubota, Fusao; Nakano, Masamoto; Tomita, Masao; Koteda, Tsunetoshi; Ayabe, Hiroyoshi (Nihon Kyōbu Shikkan Gakkai zasshi, 1974)
The patient, 32 year old male, visited the clinic with the complaint of cough, sputum and slight fever. By X-ray examinations of the chest the round shadow was found in the right lower lung field and was suspected the pulmonary benign tumor of the lung. The results of operation revealed the liver herniation encapsulated with peritoneum and with parietal pleura into the thorax through the defect of the right side diaphragm.